Makna lirik lagu "AJARKAN AKU - Jai nuardin (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2022)
This study aims to describe the denotation and connotation of the lyrics of the song "AJARKAN AKU" by Arvian Dwi. The formulation of the problem studied in the lyrics of this song is the meaning of denotation and connotation in the lyrics of the song "AJARKAN AKU" by Arvian Dwi. The method used is a qualitative descriptive method which explores the meaning of denotation and connotation. At the stage of data collection techniques using expression analysis. The data analysis technique uses the theory of Roland Barthes. The conclusion of the meaning of Denotation in the lyrics of the song " AJARKAN Aku " by Arvian Dwi is a message from Arvian Dwi's feelings to his music listeners, in a significant way Arvian Dwi conveys his experiences and feelings to his music listeners. And for the connotation meaning in the song " AJAR AKU " by Arvian Dwi Aku " by Arvian Dwi, how to forget someone without having someone is difficult, because people who inhabit someone's heart for a long time will definitely find it difficult to forget someone and coupled with forgetting someone it's not very easy.